Vidas negras e o livro didático: as Ciências da Natureza que estudam (qual) vida? - Jardim, Fabiola de Carvalho (Universidade Federal de São Carlos, 2022)
The present work has as its starting point our professional and personal experience, in which we recognize the complexity of the educational process. Each student has an ancestry, a culture, beliefs, religions or absence of faith, different ways of eating, relating, living, being, socializing, which should be present in school. One of the reasons why the different ways of being are not considered is the racism that affects the curriculum and teaching materials. Considering that the studies of the natural sciences are important for us to appropriate knowledge of intra and extra corporeal cycles and natural phenomena, but also to have real conditions to take care of ourselves, to interact with the environment in a healthy, sustainable way, preserving the right to all lives and citizenship for all, we wonder how the textbooks of Natural Sciences/Biology, since it is the science that studies all forms of life, has approached the different manifestations of life, recognizing its diversity and complexity. We have used a racial perspective to analyze three textbooks of Natural Sciences/Biology, used in public high schools in the State of São Paulo. We carried out a literature review on natural science/biology textbooks and the approach to the theme of race; we approach the notion of human race, in the biological, sociological perspective and its resignification by the black movement, as well as the science curriculum and the education of ethnic-racial relations. We rely on authors such as Verrangia (2009, 2010, 2020), Monteiro (2010), Monteiro e Pinheiro (2016), Krasilchik (1987, 2000, 2004) in relation to the teaching of science and the education of ethnic-racial relations; we turn to Maldonado-Torres (2007, 2018), Gomes (2012, 2019) and Gomes e Munanga (2006) on curriculum coloniality and, on being black and the construction of the other as non-being, to Mbembe (2014, 2017, 2018) and Carneiro (2005). With Domingos (2011, 2017), we brought human life from an African cosmovision. For the analysis of textbooks, we performed the description and recording of the observed facts, analysis and ordering (PRODANOV; FREITAS, 2013). Images were selected, by direct identification, of black human lives, human bodies or parts of them. The selection and analysis of the images of human lives present in the Textbooks of Natural Sciences/Biology, showed that only 18% of the images were of black human lives. We emphasize that in addition to the low representation, the images of black human lives were associated, for example, with the study of animals. An image of a black child with the face marked in half was used to exemplify animal symmetry. The analysis of the books revealed the permanence of racism, remnants of colonialism, the appreciation of white human life as a reference standard for human beings and humanity. We conclude that, by placing black human life in a place of invisibility, the analyzed books contribute to the maintenance of epistemic racism. We confirm that the raciality/biopower device acts through the gears of knowledge and power, which still operate as a legacy of colonialism, in the production and social reproduction of education/knowledge, as well as in subjectivities.
Black lives and the textbook: the Nature Sciences that study (what) life?
Keywords: Ensino de ciências; Ensino de Biologia; Raça; Livro didático de Ciências da Natureza/Biologia; Educação para as relações étnico-raciais; Science teaching; Biology Teaching; Race; Textbook of natural sciences/Biology; Education for Ethnic-Racial Relations; CIENCIAS HUMANAS